Primary central nervous system germ cell tumors in Central America and the Caribbean Region: an AHOPCA 20-year experience - Girón, Ana Verónica; Blanco-Lopez, Jessica; Calderon, Patricia; Jiron, Reyna; Pineda, Estuardo; Montero, Margarita; Lizardo, Yamel; Bartels, Ute; Osorio, Diana S. (Frontiers in Oncology, 2024)
BACKGROUND: Primary Central Nervous System Germ Cell Tumors (GCT) are rare neoplasms in pediatrics. Treatment depends on histological subtype and extent of disease. Overall survival (OS) is above 90% for germinomas and 70-80% for non-germinomatous GCT (NGGCT) in high-income countries (HIC) while data is usually lacking for patients in LMIC. OBJECTIVE: To describe the experience in treating patients with CNS GCT in 4 of 8 countries, members of the Asociación de Hemato-Oncología Pediátrica de Centro América (AHOPCA), and determine their 5-year OS. DESIGN/METHODS: We conducted a retrospective chart review of patients treated for CNS GCT. Epidemiological, clinical characteristics, histology, treatment modalities and outcome were analyzed. RESULTS: From 2001 to 2021, 48 patients were included; Guatemala: 22, Nicaragua: 18, Dominican Republic: 3 and El Salvador: 5. Thirty-one (64.5%) were male, median age at diagnosis was 10.2 years (range 1 to 17 years). Presenting symptoms were headaches (n=24, 50%), visual disturbances (n=17, 35.4%), vomiting (n=12, 25%), nausea (n=8, 16.7%) and diabetes insipidus (n=7, 14.6%). Two patients with NGGCT presented with precocious puberty. Biopsy or tumor resection was performed in 38 cases (79.2%); 23 (88.4%) germinomas, 11 (78.6%) NGGCT and 4 (50%) CNS GCT. Eight patients were diagnosed and treated based on CSF tumor marker elevation; four germinomas (BHCG 11.32-29.41mUI/mL) and four NGGCT (BHCG 84.43-201.97mUI/mL or positive AFP>10 UI/mL). Tumor locations included suprasellar (n=17, 35.4%), pineal (n=13, 27.1%), thalamus/basal ganglia (n=5, 10.4%), other (n=12, 25%); and one bifocal. Four (8.3%) had metastatic disease, 6 with positive CSF, staging data was incomplete in 25 patients (52%). Patients were treated with varied chemotherapy and radiotherapy modalities. Nine patients had incomplete data regarding treatment. Five-year OS was 65%, (68% for germinoma, 50.6% for NGGCT and 85.7% for unclassified-GCT). CONCLUSIONS: Germinoma was the most common histology and there was a male predominance. More than half of patients had incomplete staging data and treatment was variable across the region. OS is lower compared to HIC. Standardized treatment protocols will aid in adequate staging, treatment planning, prevent complications and improve survival.